Compound Angle Formulae

The important trigonometrical ratios of compound angle formulae are given below:

sin (A + B) = sin A cos B + cos A sin B

sin (A - B) = sin A cos B - cos A sin B

cos (A + B) = cos A cos B - sin A sin B

cos (A - B) = cos A cos B + sin A sin B

sin ( A + B) sin (A - B) = sin^2 A – sin^2 B = cos^2 B – cos^2 A

cos ( A + B) cos (A - B) = cos^2 A – sin^2 B = cos^2 B – sin^2 A

tan (A + B) = tan A + tan B/1 - tan A tan B

tan (A - B) = tan A - tan B/1 + tan A tan B

cot (A + B) = cot A cot B - 1/cot B + cot A

cot (A - B) = cot A + cot B + 1/cot B - cot A

tan (A + B + C) = tan A + tan B + tan C - tan A tan B tan C/1- tan A tan B - tan B tan C - tan C tan A.

Now we will learn how to use the above formulae for solving different types of trigonometric problems on compound angle.

1. Using the formula of cos (A - B) = cos A cos B + sin A sin B prove that cos (π/2 - x) = sin x, for all real numbers x.

Proof:

cos (π/2 - x) = cos π/2 cos x + sin π/2 sin x, [Applying the formula of cos (A - B) = cos A cos B + sin A sin B]

= 0 × cos x + 1 × sin x, [Since we know that cos π/2 = 0 and sin π/2 = 1]

= 0 + sin x

= sin x                        Proved

Therefore cos (π/2 - x) = sin x.

 

2. Using the formula of cos (A + B) = cos A cos B - sin A sin B prove that cos (π/2 + x) = - sin x, for all real numbers x.

Proof:

cos (π/2 + x) = cos π/2 cos x - sin π/2 sin x, [Applying the formula of cos (A + B) = cos A cos B - sin A sin B]

= 0 × cos x - 1 × sin x, [Since we know that cos π/2 = 0 and sin π/2 = 1]

= 0 - sin x

= - sin x                        Proved

Therefore cos (π/2 + x) = - sin x

 

3. Using the formula of sin (A + B) = sin A cos B + cos A sin B prove that sin (π/2 + x) = cos x, for all real numbers x.

Proof:

sin (π/2 + x) = sin π/2 cos x + cos π/2 sin x, [Applying the formula of sin (A + B) = sin A cos B + cos A sin B]

= 1 × cos x + 0 × sin x, [Since we know that sin π/2 = 1 and cos π/2 = 0]

= cos x + 0

= cos x                        Proved

Therefore sin (π/2 + x) = cos x

 

4. Using the formula of sin (A - B) = sin A cos B - cos A sin B prove that sin (π/2 - x) = cos x, for all real numbers x.

Proof:

sin (π/2 - x) = sin π/2 cos x - cos π/2 sin x, [Applying the formula of sin (A - B) = sin A cos B - cos A sin B]

= 1 × cos x - 0 × sin x, [Since we know that sin π/2 = 1 and cos π/2 = 0]

= cos x - 0

= cos x                        Proved

Therefore sin (π/2 - x) = cos x








11 and 12 Grade Math

From Compound Angle Formulae to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.